APPLICATION OF ADVANCED VISUALIZATION & ARTIFICIAL INTELLIGENCE TECHNOLOGY AS A CONDITION MONITORING TOOL - Efe Peter Iyomi; Isaque Moyses Guimaraes; Olutayo Opeyemi Ogunmilua; Edidiong Uboho (International Journal of Innovations in Engineering Research and Technology, 2022)
With the rapid technological advancement in the industry, systems are becoming more complex to maintain while faulty detections and diagnostics methods are becoming increasingly difficult with new technological approaches posing challenges for effective machine monitoring and deployment of maintenance strategies.Most maintenance strategies are deployed manually which means maintenance plans are pre-arranged, and this usually leads to either over maintenance or under maintenance of the asset. Therefore, an advanced optimization of maintenance plans is needed for an improved maintenance procedures and integrated assets management systems.To overcome these challenges, this paper will introduce some advanced visualization & artificial intelligence technology methods which serve as condition monitoring tools to drive an automated maintenance strategy and it will also show the dominance of the visualization technology method and how it will directly improve production.